2002
DOI: 10.1520/jfs15228j
|View full text |Cite
|
Sign up to set email alerts
|

Hair Analysis of Seven Bodybuilders for Anabolic Steroids, Ephedrine, and Clenbuterol

Abstract: Several bodybuilders, all winners of international competitions, were arrested for trafficking of a number of doping agents including anabolic steroids, ephedrine, beta-adrenergics, human chorionic gonadotropin, antidepressants, and diuretics. In accordance with the recent French law against doping, the judge asked to test seven bodybuilders to identify doping practices. Hair and urine specimens were collected for analysis. After decontamination, a 100 mg hair strand was pulverized in a ball mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…In this context, it should be kept in mind that several studies have identified an association between the use of AAS and ephedra products [26][27][28][29][30][31][32][33][34][35][36][37]. In fact, the use of AAS has been associated with the use of a wide range of illicit drugs and psychoactive pharmaceuticals [38][39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it should be kept in mind that several studies have identified an association between the use of AAS and ephedra products [26][27][28][29][30][31][32][33][34][35][36][37]. In fact, the use of AAS has been associated with the use of a wide range of illicit drugs and psychoactive pharmaceuticals [38][39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…The FDA must test meat stated for human consumption. In athletes, the drug is rapidly metabolized and is often present at only trace levels making it difficult to assay [3,9,10,11,12]. For these reasons there is much interest in methods of assay for clenbuterol that are not only highly sensitive and selective [13,14], but amenable to automation and high throughput as well.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] A variety of drugs and endogenous substances have been accurately measured in hair, including: opiates, barbiturates, benzodiazepines, anabolic steroids, cocaine, nicotine and recently, cortisol and cortisone. [21][22][23][24][25] In clinical settings, hair drug levels have been used to assist in therapeutic drug monitoring. 24 A limited number of studies by the same principle authors have examined the incorporation and detection of cortisol in human hair.…”
mentioning
confidence: 99%